THE DUSTYWINGS IN CRETACEOUS BURMESE AMBER (INSECTA: NEUROPTERA: CONIOPTERYGIDAE) - Engel M.S. (My University, 2004)
The dustywing fauna (Neuroptera: Coniopterygidae) of Upper Albian Burmese amber is revised. Two species are recognised, one belonging to the subfamily Aleuropteryginae and one to the Coniopteryginae. The aleuropterygine species is placed in the genus Glaesoconis (Glaesoconis baliopteryx sp. nov.), a previously known fontenelleine genus from New Jersey and Siberian ambers. The apparent coniopterygine differs in several features of wing venation and is therefore placed in its own tribe: Phthanoconini nov. (Phthanoconis burmitica gen. et sp. nov.). A revised key to Cretaceous dustywing genera is provided.
Keywords: ALEUROPTERYGINAE; CONIOPTERYGINAE; MYANMAR; NEUROPTERIDA; PLANIPENNIA; TAXONOMY; Albian; Mesozoic::Cretaceous::Lower::Albian; Мезозой::Меловая::Нижний::Альбский